KARAKTERISASI KOMPOSISI KIMIA DAN POTENSI PEMANFAATAN CAMPURAN TANAH GAMBUT KALIMANTAN TIMUR DENGAN FLY ASH DAN BOTTOM ASH UNTUK PERTANIAN - Imran; Hanum, Farrah Fadhillah; Setya Wardhana, Budi; Eka Suharto, Totok; Vada Febriani, Annisa (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2024)
The utilization of coal combustion waste, specifically fly ash and bottom ash, as a soil amendment offers an opportunity to enhance the fertility of peat soils in East Kalimantan, which typically have low levels of essential nutrients such as nitrogen (N), phosphorus (P), and potassium (K). This study aims to evaluate the impact of adding coal ash on peat soil's chemical composition and quality as a growing medium. The chemical composition analyzed includes alumina (Al₂O₃), silica (SiO₂), phosphorous anhydride (P₂O₅), iron(III) oxide (Fe₂O₃), and calcium oxide (CaO). X-ray Fluorescence (XRF) was used to determine changes in nutrient content. The results indicate that adding coal ash increases the levels of potassium (K) and silica (SiO₂), but decreases the levels of nitrogen (N) and phosphorus (P₂O₅). Additionally, adding coal ash affects soil pH, which impacts nutrient availability. These findings indicate that while coal ash can enhance soil enrichment with potassium and silica, its impact on nitrogen, and phosphorus must be carefully managed to optimize fertilization and promote healthy plant growth.